STUDI KASUS PENGUASAAN SENGKETA TANAH MARTUBUNG DARI ASPEK HUKUM PIDANA - Bella Ayu Anzalia; Martua Felix Jonatan Simanullang, Halimah, Reh Bungana Beru Prangin-Angin, Maulana Ibrahim (JOURNAL OF LAW AND NATION, 2023)
This research aims to resolve the settlement of control over Martubung land from the criminal law aspect. This research uses methods to study land landscapes in rural areas and understand the dynamics of the land. We conducted comprehensive interviews with two participants representing various parties involved in the anomaly, such as landowners, rights claimants, and their family members. Based on the results of our discussion and research, it can be concluded that the placement of land settlement settlement rooms is regulated because land settlement settlements are often carried out in general judicial institutions. Every match is often brought by the community to seek justice. For those seeking justice in general